INFLUENCE OF RISK ASSESSMENT ON SECURITY MANAGEMENT OUTCOMES IN PUBLIC SECONDARY SCHOOLS IN MANDERA COUNTY, KENYA - Daud, Abdi; Thinguri, Ruth; Mugwe, Dr. Mary (African Journal of Education and Practice, 2022)
Purpose: There is present fear on the swelling incidents of disasters in institutions in this country which makes it necessary to explore the risk assessment in schools. The aim of this research was to explore the influence of risk assessment on security management outcomes in public secondary schools in Mandera County, Kenya. Methodology: Theories guiding the study were the Stakeholders' and the Securitization theories. The investigation employed mixed methodology and the concurrent triangulation design. The target population was 400 participants and involved principals, teachers and education officers. This included all the secondary schools and all the 18 education officers in Mandera County and the 58 principals, 324 teachers. Questionnaires were used for teachers while interviews were used for principals on security management outcomes. Quantitative data were analyzed in descriptive statistics and presented by tables, frequencies and percentages. Qualitative data were analyzed by thematically in narrative forms and verbatim citations. Two levels of analysis were employed namely: descriptive and thematic. Findings: From the research findings, it was clear that there were efforts made to assess risks but there was also need to beef up the same since it was not adequately done. There was lack of visits from the government to enhance safety of students in schools. Unique Contribution to Theory, Policy and Practice: The stakeholders' and the securitization theories were used to alert schools and prepare them for calamities consecutively hence contributing to the issues in the study. The study established that risk assessment needed to be prioritized in spite of the fact that some efforts were being made. It was concluded that more efforts be put on risk assessment. The theories were validated in that there was sensitization to stakeholders and the need to prepare in advance for disasters in schools. It was recommended that the Ministry of Education be active in doing necessary checks on risk assessment and be sending security teams in schools